Efektivitas Minuman Kelapa untuk Mempercepat Rehidrasi dan Pemulihan Pasca Latihan pada Atlet Futsal Remaja Putra: Effectiveness of Coconut Drink to Accelerate Rehydration and Post-Training Recovery in Male Futsal Athlete - Sumule, Jordan Tirto; Setiawan, Budi; Dewi, Mira (Jurnal Ilmu Gizi dan Dietetik, 2025)
This study aimed to analyze the effect of coconut drink on rehydration status and post-exercise recovery in male adolescent futsal athletes. The coconut drink is made by blending coconut flesh and water using a blender. The coconut variety used is dwarf coconut with the fruit being 6 to 8 months old. The coconut drink was given to male adolescent futsal athletes after a training session to determine its effectiveness in restoring their hydration and energy status. This study used a cross-over design and involved 22 subjects. The subjects were male adolescent futsal athletes aged 16-18 years. A total of 22 subjects were then divided into two groups of 11 subjects. Each group was given a different drink in the third week. The drinks used in this study consisted of coconut drink and bottled mineral water. A washout period was given in the second week to neutralize the effects of the administration received during the first week. Measurement of hydration status used body weight before and after training. Rehydration status was obtained by measuring weight gain after being given coconut drink. Energy recovery was measured by maximum push-up power ability and sprint speed ability over a distance of 35 m. Blood pressure and heart rate were recorded before and after exercise and after being given coconut drink to determine the benefits of coconut drink in restoring the body's condition after exercise to normal. The assessment of the sensation of the drink after consumption after exercise consisted of thirst, bloating, nausea, feeling of being unwell, and fatigue. The results showed no significant difference between coconut drink (p=0.15) and bottled mineral water (p=0.35) in improving the hydration status of athletes. However, coconut drink was better at restoring blood pressure, heart rate, and energy recovery (p>0.05). Coconut drink had a better effect on the perception of drink sensation than bottled mineral water (p>0.05).